2017
DOI: 10.7869/djo.242
|View full text |Cite
|
Sign up to set email alerts
|

Optic Disc Pit Maculopathy (ODP-M) Surgical Intervention and Outcome

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…After that, the Adding tripolyphosphate (TPP) to the solution of the mixture of plant extract and chitosan at a ratio of 2.5:1 (% w/w) with continuous stirring and agitation at room temperature for 6 hours, reaching the equilibrium state represented by obtaining a viscous consistency with a distinctive color for the mixture, which represents the formation of nanoparticles and obtaining On the nanocomposite (methanolic extract of pumpkin peels with nano chitosan (Cu/Cs-NPs). The nanoparticles were separated from the liquid by centrifugation at 16,000 (revolutions/min) for an hour, the solution was filtered, and the precipitated portion was washed several times with deionized water, then dried and preserved until use [11]. Base solutions of the methanolic extract with nano chitosan (Cu/Cs-NPs nanocomposite) were prepared at two concentrations of 32 and 16 mg/mL, after which they were stored in dark amber glass bottles at 4°C until use.…”
Section: Preparation Of Pumpkin Peel Extract Loaded With Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, the Adding tripolyphosphate (TPP) to the solution of the mixture of plant extract and chitosan at a ratio of 2.5:1 (% w/w) with continuous stirring and agitation at room temperature for 6 hours, reaching the equilibrium state represented by obtaining a viscous consistency with a distinctive color for the mixture, which represents the formation of nanoparticles and obtaining On the nanocomposite (methanolic extract of pumpkin peels with nano chitosan (Cu/Cs-NPs). The nanoparticles were separated from the liquid by centrifugation at 16,000 (revolutions/min) for an hour, the solution was filtered, and the precipitated portion was washed several times with deionized water, then dried and preserved until use [11]. Base solutions of the methanolic extract with nano chitosan (Cu/Cs-NPs nanocomposite) were prepared at two concentrations of 32 and 16 mg/mL, after which they were stored in dark amber glass bottles at 4°C until use.…”
Section: Preparation Of Pumpkin Peel Extract Loaded With Nanoparticlesmentioning
confidence: 99%
“…The green synthesis of nano chitosan with the methanolic extract of pumpkin peels was characterized by °, 32.14°, 37.30°, 39.32°, 45.05°), on the other hand, Figure (11) shows the X-ray diffraction patterns of chitosan. The results showed that the 2θ value for chitosan at its main peak was 20.53° and an intensity level close to (1200 cont.…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 99%